Analisis Kritis Terhadap Kebijakan Percepatan Investasi Dan Kemudahan Berusaha di Era Otonomi Daerah - Aziz Widhi Nugroho; Lita Tyesta Addy; Listya Wardhani (Universitas Negeri Semarang, 2020)
The government is pushing for an increase in the pace of investment by organizing the Investment Award activities in 2018. The Wonogiri Regency Government shows proud results with the ISO 9001: 2015 rating, this has an impact on the investment rates that are being applied by the region for anyone who wants to contribute to investing in Wonogiri. Pro investment policies that have been proven by the district government need to be accompanied by improved regulations that do not hamper the rate of investors investing in Wonogiri. Regulations that are more easily supported by the OSS (Online Single Submissions) system, should make it easier for businesses to try in Wonogiri. This is important in order to increase employment opportunities and Regional Original Revenues which affect development, both physical and non-physical aspects. Adequate infrastructure development can increase economic growth that can increase investors entering Wonogiri. This study uses normative juridical with the consideration that the starting point of research analysis of laws and regulations that open opportunities for mal administration. The plan, prepared by the government, will add locations for the designation of industrial estates, which in total number 14 sub-districts. This needs to be prepared carefully related to the place that is intended for the industrial zone in order to attract foreign and local investors.